(untitled) (Scientific journal of the Fergana State University, 2024)
Many mechanisms of the body’s vital activity have been discovered to date. With regard to the energy of warm-blooded animals, the mechanism of tissue heat production has not been finally established. Having a powerful energy basis, this process is aimed at warming the body, which spends up to 80-90% of the body’s energy, i.e. it has a tremendous effect on the body’s metabolism. These energy costs can be used for the benefit of human. In particular, one should learn how to regulate its activity, which will increase the efficiency of biological processes. The entire body can receive energy support because of increased efficiency that can improve recovery processes in the event of heavy physical exertion on the body or the presence of pathological weakening of certain metabolic links in tissues. The use of uncoupled respiration as a factor with positive practical possibilities has many prospects that are waiting in the wings for their implementation. All the above indicates the need to develop this area of research and to refine this problem. We believe that there are sufficient conditions for conducting research in this direction.